2011
DOI: 10.1021/jp110423w
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Methyl Iodide Adsorption and Dissociation on Clean and K-Promoted β-Mo2C Surfaces

Abstract: ABSTRACT:We have studied the effect of K on the adsorption and dis sociation of methyl iodide on the β-Mo 2 C(001) surface using density functional theory calculations, and the results were compared with experimental data. The most favorable sites for methyl iodide adsorption are 3-fold sites on both clean and K-promoted surface. The changes in the work function fit our model as the molecule withdraws charge from the surface. The C-I bond weakens when the molecule adsorbs on the surface, and this effect is mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Although the reactions of different molecules on K-doped Mo 2 C surfaces were successfully modeled by our group with DFT calculations, resulting in reasonably well coincidence with experimental findings, the detailed modeling of alkali modifier for CO interaction with Mo 2 C surfaces is still lacking. In the present work, the reaction pathway of CO decomposition in the presence of potassium on molybdenum- and carbon-terminated β-Mo 2 C single crystals is modeled using DFT.…”
Section: Introductionmentioning
confidence: 65%
“…Although the reactions of different molecules on K-doped Mo 2 C surfaces were successfully modeled by our group with DFT calculations, resulting in reasonably well coincidence with experimental findings, the detailed modeling of alkali modifier for CO interaction with Mo 2 C surfaces is still lacking. In the present work, the reaction pathway of CO decomposition in the presence of potassium on molybdenum- and carbon-terminated β-Mo 2 C single crystals is modeled using DFT.…”
Section: Introductionmentioning
confidence: 65%
“…In addition to the experimental investigations, there are also theoretical studies on the catalytic properties of Mo 2 C. Liu et al demonstrated the key role of the surface carbon atoms on the orthorhombic Mo 2 C in the catalytic dissociation of sulfur containing compounds based on density functional theory (DFT) calculations. Theoretical studies on the adsorption and decomposition of methanol, , methyl iodide, and CO as well as potassium promoting effect on the orthorhombic Mo 2 C were systematically reported by Pistonesi et al, and they found that the incorporation of potassium atoms enhances the dissociation ability of the C–I and C–O bonds in CH 3 I and CH 3 OH but increases the CO dissociation barrier.…”
Section: Introductionmentioning
confidence: 97%
“…Due to their high importance in heterogeneous catalysis, there are many theoretical studies about the terminations, adsorption properties and reactions on the surfaces of the orthorhombic, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] hexagonal eclipsed 26,[45][46][47] and hexagonal CdI 2 -antitype [48][49][50][51] structures. For understanding the catalytic properties of these individual structures we studied the fundamental aspects of these catalysts.…”
Section: Introductionmentioning
confidence: 99%